2022
DOI: 10.3390/w14050755
|View full text |Cite
|
Sign up to set email alerts
|

A New Evolutionary Hybrid Random Forest Model for SPEI Forecasting

Abstract: State-of-the-art random forest (RF) models have been documented as versatile tools to solve regression and classification problems in hydrology. They can model stochastic time series by bagging different decision trees. This article introduces a new hybrid RF model that increases the forecasting accuracy of RF-based models. The new model, called GARF, is attained by integrating genetic algorithm (GA) and hybrid random forest (RF), in which different decision trees are bagged. We applied GARF to model and forec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The authors reported the NSE values of their best models equal to 0.49 and 0.53, which are significantly lower than those in this study. Similarly, the VMD-GP model provided more accurate predictions than the RF model optimized by the genetic algorithm developed by Danandeh Mehr et al [53] for SPEI-3 prediction at Beypazari (NSE = 0.50) and Nallihan (NSE = 0.61) cities in Turkey. Despite the greater performance of the VMD-GP over GP and GEP, our study showed noticeable limitations in attaining an ideal forecast (i.e., NSE > 0.9).…”
Section: Discussionmentioning
confidence: 87%
“…The authors reported the NSE values of their best models equal to 0.49 and 0.53, which are significantly lower than those in this study. Similarly, the VMD-GP model provided more accurate predictions than the RF model optimized by the genetic algorithm developed by Danandeh Mehr et al [53] for SPEI-3 prediction at Beypazari (NSE = 0.50) and Nallihan (NSE = 0.61) cities in Turkey. Despite the greater performance of the VMD-GP over GP and GEP, our study showed noticeable limitations in attaining an ideal forecast (i.e., NSE > 0.9).…”
Section: Discussionmentioning
confidence: 87%
“…More recently, Danandeh Mehr et al [103] presented a new forecasting model referred to as GARF, which is the integration of genetic algorithm and RF. SPEI values with 3-and 6-month timescales, which were calculated for Nallihan and Beypazari stations, were used to examine the GARF model forecast capabilities.…”
Section: Review Of Drought Forecasting Studiesmentioning
confidence: 99%
“…Due to the complexity and non-linearity of the drought process, simulations using non-linear time series data are necessary. Consequently, machine learning (ML) systems for drought forecasting have attracted considerable interest [14,15]. In addition, several types of research have shown that AI algorithms outperform conventional approaches [16][17][18][19], such as artificial neural network (ANN) [20], support vector machines (SVMs) [21], random forests [22], and the adaptive neuro-fuzzy inference system (ANFIS) [23], which are examples of these ML systems.…”
Section: Introductionmentioning
confidence: 99%